2019
DOI: 10.1186/s12933-019-0895-0
|View full text |Cite
|
Sign up to set email alerts
|

Carotid ultrasound investigation as a prognostic tool for patients with diabetes mellitus

Abstract: Background Experimental and clinical data indicate a major influence of diabetes on atherogenesis. We aimed to assess whether the effect of diabetes on long-term mortality in asymptomatic patient with carotid stenosis is contingent upon the degree of the carotid atherosclerotic burden. Methods 1065 patients with neurological asymptomatic carotid atherosclerosis as evaluated by duplex sonography were prospectively followed for cause-specific mortality. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
17
0
2
Order By: Relevance
“…Similar findings were observed in another study involving 1,065 patients with neurological asymptomatic carotid atherosclerosis (median follow up: 11.8 years) (7). DM was diagnosed in 335 (31.5%) of the participants; most had T2DM (95.3%).…”
Section: Glycaemic Control and Carotid Diseasesupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings were observed in another study involving 1,065 patients with neurological asymptomatic carotid atherosclerosis (median follow up: 11.8 years) (7). DM was diagnosed in 335 (31.5%) of the participants; most had T2DM (95.3%).…”
Section: Glycaemic Control and Carotid Diseasesupporting
confidence: 87%
“…DM was diagnosed in 335 (31.5%) of the participants; most had T2DM (95.3%). In this study, the adjusted hazard ratio (HR) for every 1% increase in glycated haemoglobin (HbA 1c ) levels was 1.31 (P<0.01) for cardiovascular (CV) mortality and 1.21 (P<0.01) for all-cause mortality, respectively (7).…”
Section: Glycaemic Control and Carotid Diseasementioning
confidence: 68%
“…Carotid ultrasonography is one of the assessment procedures for atherosclerosis and has several advantages, such as noninvasiveness, simplicity, inexpensiveness, and reproducibility. Moreover, it was reported that it could be a prognostic tool for patients with diabetes [ 6 ]. Due to these advantages, the indices of carotid ultrasonography have been used as a marker of atherosclerosis in previous clinical studies [ 7 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The thickening of intima-media determined via carotid duplex also facilitates CVD prognostication in asymptomatic scenarios. There is now an advocation to use the results of a carotid duplex in anticipating long-term mortality in neurologically asymptomatic diabetic patients with CVD/carotid arteriosclerosis [23]. This is because the results obtained from carotid duplex screening have a high validity and reliability making it a preferred diagnostic modality for evaluating the risk and prognosis of atherosclerosis in the setting of CVD [24].…”
Section: Carotid Duplexmentioning
confidence: 99%